The Fast Spiking Subpopulation of Striatal Neurons Coding for Temporal Cognition of Movements - Shen, Bo; Wang, Zuo-Ren; Wang, Xiao-Ping (Frontiers in Cellular Neuroscience, 2017)
Background: Timing dysfunctions are presented by a number of neurological and psychiatric disorders such as Parkinson’s disease, obsessive compulsive disorder, autism and attention deficit/hyperactivity disorder. Several lines of evidence supporting specific fronto-striatal abnormalities involve the timing process. The striatum is known to encode reinforcement learning and procedural motion, and consequently is required to represent temporal information precisely which guides actions in proper sequence. Previous studies highlighted the temporal scaling property of timing-relevant striatal neurons; however, it is still unknown how this is accomplished over short temporal latencies like sub-seconds to seconds range. Methods: A series of timing behavior task was designed that required rats to reproduce a fixed duration robust action. Using chronic multichannel electrode array, we recorded neural activity from dorsomedial striatum in 4 rats performing the task and identified modulation response of each neuron to different events. Cell type classification was performed according to a multi-criteria clustering analysis. Results: 557 dorsomedial striatal neurons were recorded, of which 113 single units, especially the fast-spiking subpopulation, which had trial to trial ramping up or ramping down firing modulation during the time estimation period were considered as timing-relevant neurons. Furthermore, these timing-relevant striatal neurons might calibrate the spread of their firing pattern by rewarded experience to make the timing behavior accurately. Conclusions: Our data implied that the dynamic activities of such timing-relevant units embodied both the current duration and recent outcomes information to predict and drive the following action. These results reveal the potential mechanism of time calibration in a short temporal resolution, which may help to explain the neural basis of motor coordination affected by certain physiological or pathological conditions.